2023
DOI: 10.1038/s42004-022-00800-6
|View full text |Cite
|
Sign up to set email alerts
|

Appearance and suppression of Turing patterns under a periodically forced feed

Abstract: Turing instability is a general and straightforward mechanism of pattern formation in reaction–diffusion systems, and its relevance has been demonstrated in different biological phenomena. Still, there are many open questions, especially on the robustness of the Turing mechanism. Robust patterns must survive some variation in the environmental conditions. Experiments on pattern formation using chemical systems have shown many reaction–diffusion patterns and serve as relatively simple test tools to study genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The effect of a sinusoidal forcing on the input feed composition was recently explored experimentally and numerically using simplified models. [ 20 ] In this study, we used a chemically realistic mechanism that includes a reaction responsible for differential diffusion. In the 2D description of the TSFR, we only neglected the feedback of the gel composition on that of the tank.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of a sinusoidal forcing on the input feed composition was recently explored experimentally and numerically using simplified models. [ 20 ] In this study, we used a chemically realistic mechanism that includes a reaction responsible for differential diffusion. In the 2D description of the TSFR, we only neglected the feedback of the gel composition on that of the tank.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, another method, periodic feeding from the boundary, was applied in a TSFR in similar chlorite‐iodide‐malonic acid (CIMA) reaction. [ 20 ] The experiments showed that patterns may appear and persist under periodic environmental conditions. Theoretical studies on the time‐periodic forcing of Turing patterns near a Turing‐Hopf bifurcation point presented that forcing may enhance or suppress Turing patterns, in agreement with the experimental observations.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, one of the most essential problems in this context is to study the response behaviours of patterns with respect to an external stimulus. [11][12][13][14][15][16][17][18] The external spatial force provides a powerful way to investigate the wavenumber selection mechanism and the controlling mechanism of spatial structures. 14,15 During the past two decades, studies on the effects of spatially periodic force have concentrated on Turing patterns in reaction diffusion systems that undergo Turing instability.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, one of the most essential problems in this context is to study the response behaviours of patterns with respect to an external stimulus. 11–18 The external spatial force provides a powerful way to investigate the wave-number selection mechanism and the controlling mechanism of spatial structures. 14,15…”
Section: Introductionmentioning
confidence: 99%
“…[5][6] Recently, chemists also generated LP in several synthetic systems based on nanoparticle assembly in hydrogel matrix mediated by pH gradient or modulating the surface charge of interacting species to achieve stationary inhomogeneous but controlled distribution of particle deposition in space. [7][8][9][10] In this context, spatial transport can also be governed by applying energy in addition to diffusion. 11 Therefore, many metastable or transiently stable state in a chemical process can be transported by applying energy and thus information can be stored in a different zone.…”
mentioning
confidence: 99%